Roles of RAGE/ROCK1 Pathway in HMGB1-Induced Early Changes in Barrier Permeability of Human Pulmonary Microvascular Endothelial Cell - Zhao, Meng-jiao; Jiang, Hao-ran; Sun, Jing-wen; Wang, Zi-ang; Hu, Bo; Zhu, Cheng-rui; Yin, Xiao-han; Chen, Ming-ming; Ma, Xiao-chun; Zhao, Wei-dong; Luan, Zheng-gang (Frontiers in Immunology, 2021)
Background: High mobility group box 1 (HMGB1) causes microvascular endothelial cell barrier dysfunction during acute lung injury (ALI) in sepsis, but the mechanisms have not been well understood. We studied the roles of RAGE and Rho kinase 1 (ROCK1) in HMGB1-induced human pulmonary endothelial barrier disruption. Methods: In the present study, the recombinant human high mobility group box 1 (rhHMGB1) was used to stimulate human pulmonary microvascular endothelial cells (HPMECs). The endothelial cell (EC) barrier permeability was examined by detecting FITC-dextran flux. CCK-8 assay was used to detect cell viability under rhHMGB1 treatments. The expression of related molecules involved in RhoA/ROCK1 pathway, phosphorylation of myosin light chain (MLC), F-actin, VE-cadherin and ZO-1 of different treated groups were measured by pull-down assay, western blot and immunofluorescence. Furthermore, we studied the effects of Rho kinase inhibitor (Y-27632), ROCK1/2 siRNA, RAGE-specific blocker (FPS-ZM1) and RAGE siRNA on endothelial barrier properties to elucidate the related mechanisms. Results: In the present study, we demonstrated that rhHMGB1 induced EC barrier hyperpermeability in a dose-dependent and time-dependent manner by measuring FITC-dextran flux, a reflection of the loss of EC barrier integrity. Moreover, rhHMGB1 induced a dose-dependent and time-dependent increases in paracellular gap formation accompanied by the development of stress fiber rearrangement and disruption of VE-cadherin and ZO-1, a phenotypic change related to increased endothelial contractility and endothelial barrier permeability. Using inhibitors and siRNAs directed against RAGE and ROCK1/2, we systematically determined that RAGE mediated the rhHMGB1-induced stress fiber reorganization via RhoA/ROCK1 signaling activation and the subsequent MLC phosphorylation in ECs. Conclusion: HMGB1 is capable of disrupting the endothelial barrier integrity. This study demonstrates that HMGB1 activates RhoA/ROCK1 pathway via RAGE, which phosphorylates MLC inducing stress fiber formation at short time, and HMGB1/RAGE reduces AJ/TJ expression at long term independently of RhoA/ROCK1 signaling pathway.